How Service Quality and Perceived Privacy Can Affect the Customer Satisfaction in Generations Y and Z? - M Iqbal Nurfaizi; Endy Gunanto Marsasi (Fakultas Ekonomika dan Bisnis UNTAG Semarang, 2025)
The impetus for this research is the suboptimal concept of service quality and perceived privacy toward customer satisfaction for online food delivery. This study seeks to ascertain the influence of service quality, perceived security, and privacy on enhancing customer satisfaction via SERVQUAL Theory. Data were collected by distributing questionnaires using the purposive sampling method to 190 generation Y and Z participants who used online food delivery. Data were analyzed using CB-SEM to test the relationship between latent variables through parameter estimation, hypothesis testing. The results of this study indicate that service quality and customer perceived value do not significantly affect customer satisfaction. However, this study reveals that service quality, perceived security, perceived privacy, and customer perceived value have a significant effect on trust, and trust significantly affects customer satisfaction. The novelty of the research in this study is the addition of the perceived privacy variable. The findings of this study provide insight into the development of SERVQUAL Theory. This study extends the application of the theory by adding perceived privacy and perceived security as important variables relevant to online food delivery. This study provides insight for companies to design effective marketing strategies to build trust and increase customer satisfaction.